The Influence of Transformational Leadership Style and Motivation on Employee Performance PT. Bintang Kadiri - Rinto Harno; Liosten Rianna Roosida Ully T; Putri Septi Naulina Hasibuan; Liya Rinawati (Ilomata International Journal of Management, 2023)
The purpose of this study was to ascertain the impact of motivation and a transformational leadership style on the productivity of PT. Bintang Kadiri employees in Kediri Regency, to ascertain the impact of transformational leadership style and motivation on the output of PT. Bintang Kadiri employees, and to determine the indirect impact of transformational leadership style and motivation on performance through job satisfaction of PT. Bintang Kadiri employees as well as ascertaining the impact of job satisfaction has a significant impact on the performance of the company PT. Bintang Kadiri. The goal of this study, which involved 30 respondents, was to determine how transformational leadership style and motivation affect job satisfaction and how those factors affect the performance of PT. Bintang Kadiri personnel. The study's findings for the first hypothesis led to an explanation of how PT. Bintang Kadiri employees' job satisfaction is influenced by their motivation and transformational leadership style at the same time, the second premise can be justified by showing how the motivation and leadership style of PT. Bintang Kadiri personnel have an impact on their performance, the third theory is that employees of PT. Bintang Kadiri from Motivation perform better when their leaders adopt a transformational style, and the fourth hypothesis showed the employee performance at PT. Bintang Kadiri is significantly impacted by job satisfaction.